Progresivitas Kebijakan Anti-Predatory Pricing melalui Parallel Investigation Berbasis Human Centered Design guna Melindungi Pelaku Usaha E-Commerce - Ningtias, Dera Pramudiani; Lintang Mahisi, Prawatya; Sabila, Salsa (Forschungsforum Law Journal, 2025)
ABSTRACT: Predatory pricing protection is implemented based on the principle of equal justice between business actors. One of the fulfillments of such fairness is to ensure that business actors, both large business actors and small and medium business actors have the same opportunity to compete fairly in the market. The existing condition of business competition in Indonesia has not been maximized as evidenced by the existence of unfair business competition such as predatory pricing. This practice shows that there are still business actors who utilize market dominance to get rid of competitors through strategies for the purpose of controlling the market. Therefore, a transformation is needed regarding the optimization of the role and authority of KPPU in handling unfair business competition with parallel investigation. Based on these problems, this study is intended to analyze the reality of business competition policy towards predatory pricing problems in Indonesia and examine the progressivity of business competition policy through a parallel investigation approach based on Human-Centered Design as an alternative solution in the context of protecting business actors. The method used in this research is doctrinal research with statutory, comparative, and conceptual approaches. This research will provide the results of the mechanism of parallel investigation approach based on Human-Centered Design. This study concludes that the implementation of the enforcement of rules regarding predatory pricing practices is still problematic in terms of institutional dependence on the coercive nature of other institutions. Thus, there is a need for policy progressivity and institutional authority in handling predatory pricing using parallel investigation. Keywords: Predatory Pricing, Parallel investigation, Human-Centered Design